Peran Kepemimpinan Kepala Sekolah dan Kompetensi Kewirausahaan Guru dalam Mewujudkan Kesiapan Peserta Didik Menghadapi Dunia Usaha - Novariani Indri Utami; Muhamamd Sabandi; Susi Susi (Ikatan Da'i Indonesia, 2025)
The rapid development of the global economy and the dynamics of the business world in the digital era require educational institutions to prepare students not only with academic knowledge but also with entrepreneurial readiness. This study aims to analyze the role of school leadership and teachers’ entrepreneurial competence in fostering students’ readiness to face the business and entrepreneurial world. A comprehensive literature-based approach supported by empirical findings from recent studies was employed to examine how entrepreneurial or edupreneurial leadership of school principals and teachers’ entrepreneurial competencies contribute to effective entrepreneurship education. The findings indicate that school principals with entrepreneurial leadership play a strategic role in creating an innovative learning ecosystem through policy direction, resource allocation, and collaboration with industry and local businesses. Meanwhile, teachers’ entrepreneurial competence, covering practical business skills, project-based learning design, and entrepreneurial mindset development, directly influences students’ self-efficacy, creativity, and entrepreneurial orientation. The synergy between visionary school leadership and competent teachers strengthens the implementation of experiential learning models such as Teaching Factory and project-based entrepreneurship learning, which significantly enhance students’ readiness for real-world business challenges. However, several challenges remain, including unequal resources, limited teacher training, and insufficient industry partnerships, which hinder optimal implementation in some schools. This study concludes that strengthening school leadership capacity and teachers’ entrepreneurial competence in an integrated and contextual manner is essential for improving students’ entrepreneurial readiness. The results provide important implications for educational policy and school management in developing sustainable entrepreneurship education programs that prepare graduates to become adaptive, innovative, and independent economic actors.